Analisis Strategi Digital Public Relation Bank Syariah Indonesia Pada Masa Covid-19 - Yatimi, Muh Asrul (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the Digital Public Relations (PR) strategy of Bank Syariah Indonesia during the Covid-19 pandemic. The Covid-19 pandemic presented significant challenges for various sectors, including the Islamic banking industry in Indonesia. Bank Syariah Indonesia (BSI), established in 2021, faced major internal and external challenges. However, the implementation of Sharia principles, which emphasize justice and transparency, helped BSI demonstrate better resilience compared to conventional banks during the pandemic. BSI responded to this crisis by adopting a digital public relations (PR) strategy that included external strategies through online media and internal strategies to build employee engagement. The research findings indicate that digital PR helped strengthen BSI’s positive image and increased public trust. Despite liquidity declines and rising non-performing financing (NPF) ratios, innovation in digital transformation and effective communication strategies enabled BSI to endure and grow during the crisis. With the profit-sharing system that is a hallmark of Islamic banking, BSI has a significant opportunity to capitalize on this momentum and maintain financial stability.